Toxicity Evaluation of 6-Mercaptopurine Using Accelerated Cytotoxicity Mechanism Screening (ACMS) techniques - Ahmad Salimi; Melina Rahmandoost; Jalal Pourahmad (Iranian Journal of Pharmaceutical Sciences, 2016)
6- Mercaptopurine (6-MP) is widely used in clinic as an immunosuppressive for treatment of acute lymphocytic leukemia, Crohn’s disease, and ulcerative colitis with documented unpredictable hepatotoxicity. The potential molecular cytotoxic mechanisms of 6-MP against isolated rat hepatocytes were searched in this study using ―Accelerated Cytotoxicity Mechanism Screening (ACMS)‖ techniques. The concentration of 6-MP required to cause 50% cytotoxicity in 2 hour at 37∘C was detected to be 400 μM. A significant increase in 6-MP induced cytotoxicity and reactive oxygen species (ROS) formation, % mitochondrial membrane potential (MMP), lysosomal damage were observed. The addition of chloroquine (lysosomotropic agent), L-carnitine (inhibitor of membrane permeability transition (MPT), Diphenyleneiodonium (DPI) as an inhibitor of production of superoxide, and H2O2 by mitochondria and Dimethyl sulfoxide (DMSO) as a radical scavenger decreased 6-MP-induced cytotoxicity, ROS formation, collapse of MMP, and lysosomal damage. Results from this study suggest that 6-MP -induced cytotoxicity in isolated rat hepatocytes due to ROS formation, mitochondrial and lysosomal damages that resulted in crosstalk toxicity between mitochondrial and lysosomal damage and finally cell death.